Rua da Frente: Avenida Getúlio Vargas como contexto na prostituição em São Carlos - SP - Rodrigues, André Rocha [UNESP] (2015)
This work concerns the occupation, appropriation and transformation of an urban public space by prostitution in the city of São Carlos, in the São Paulo state. It thus joins the discussion on urban spaces and the dynamics of medium-sized cities from the perspective of Urban Anthropology. The aim is to determine why, how and when Getúlio Vargas Avenue became a place of prostitution. In addition to that, I observed how São Carlos residents, especially those living near the space in question, relate to it and to the activities conducted therein. Finally, I observed the appropriation of the space by prostitutes and how this occurred. To this end, I conducted an ethnographic study in the area during the nighttime, another during daytime and I also studied it's an ethnography of a narrative. In terms of methodology, the area was approached as a context, as proposed by Roy Wagner (2012), with a focus on the relationships established within the urban space, as well as on the contacts that this space provides. Following urbanistic transformations and conflicts among the prostitutes, they went on to occupy the place and refer to it as Street. I treated the word Street as an analytical category, establishing a dialogue with the categories House, Street, Turf, Patch, Route, Circuit, and Code-Territory, showing its potential for the expansion of the reflection on the appropriation of the urban space by the subjects